Perancangan Kantor KPA ( Komisi Penanggulangan AIDS) - Atiza Nurhuzna; Henry Soleman Raubaba; Yosi Valentina Simorangkir; Muhamad Yanni (Musamus Journal of Architecture, 2020)
KPA (AIDS Adventure Commission) is a government program to control the spread of HIV / AIDS in Indonesia. Merauke is one of the districts that has a fairly large spread of HIV / AIDS in Papua Province. The role of KPA in Merauke is very much needed in tackling the spread of HIV / AIDS. The absence of a permanent KPA office in Merauke is an obstacle to work program activities. The purpose of this design is to provide a design for the KPA office in Merauke that can meet all activities and needs related to the work program of the KPA office. The method used in this preparation is the descriptive method. The process of searching for data using observation techniques, interviews and literature studies related to the KPA office. The application uses a modern tropical architectural design approach which emphasizes the use of modern materials in the building parts such as floors, walls, roofs and the application of tropical elements is used to complete the ventilation and lighting systems of the building. The design of the KPA office is located in the center of Merauke City, precisely on Ahmad Yani Street, using a modern tropical architectural design approach, which is a building design using modern materials for a modern architectural approach and the use of tropical con